1992
DOI: 10.1093/oxfordjournals.humrep.a137790
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol enhances in vitro the histamine release induced by embryonic histamine-releasing factor (EHRF) from uterine mast cells

Abstract: The relationship between maternal hormones and factors secreted by the implanting embryo is still controversial. We have analysed the in-vitro effect of oestradiol and human embryo-derived histamine-releasing factor (EHRF) on histamine release from rat uterine mast cells. Rat uterine mast cells which were preincubated with oestradiol and then challenged with human EHRF gave histamine release values two-to threefold higher than those without preincubation. The enhancement observed was time-and temperaturedepend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 2 publications
0
37
1
1
Order By: Relevance
“…during the period propitious for embryo implantation [28], The current finding that RLX lacks the capacity to mediate de novo angiogenesis in the mesen tery implies that this hormone per se does not promote abdominal pregnancies which require de novo angiogene sis. It is moreover known that a factor in blastocyts induces mast-cell secretion at implantation [29,30] and that RLX is able to inhibit mast-cell secretion intraabdominally [31]. The physiologic surge of RLX in the peritoneal fluid should thus suppress mast-cell secretion in cases of intra-abdominal blastocyst implantation.…”
Section: Discussionmentioning
confidence: 99%
“…during the period propitious for embryo implantation [28], The current finding that RLX lacks the capacity to mediate de novo angiogenesis in the mesen tery implies that this hormone per se does not promote abdominal pregnancies which require de novo angiogene sis. It is moreover known that a factor in blastocyts induces mast-cell secretion at implantation [29,30] and that RLX is able to inhibit mast-cell secretion intraabdominally [31]. The physiologic surge of RLX in the peritoneal fluid should thus suppress mast-cell secretion in cases of intra-abdominal blastocyst implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Super-physiological concentrations of estradiol (E 2 , 1-10 μM) has been shown to induce (Spanos et al, 1996;Vliagoftis et al, 1992) or inhibit (Harnish et al, 2004) mast cell degranulation. Further, preincubating basophils or mast cells with physiological concentrations of E 2 has been shown to increase the subsequent histamine release induced by cross-linking surface-bound IgE with antibodies (Cocchiara et al, 1990;Cocchiara et al, 1992). The effects of hysiological concentrations of E 2 alone and the cellular and molecular mechanism(s) underlying estrogenic effects on mediator release from mast cells require further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen promotes MC degranulation and histamine release and enhances the IgE-dependent MC activation. Since it has been shown that MCs express estrogen receptors and E 2 enhances MC degranulation by genomic and non-genomic pathways (Cocchiara et al 1992, Zaitsu et al 2006), we could not discard the hypothesis that the MCs degranulation process and the consequent VEGF increase described here could be regulated by E 2 . Further investigations are necessary to elucidate this event.…”
Section: Discussionmentioning
confidence: 73%